Characterization of Underlying Twin Shield Tunnels Due to Foundation-Excavation Unloading in Soft Soils: An Experimental and Numerical Study - Xiaodong Cheng (MDPI AG, 2021)
Excavation near or above existing shield tunnels often results in adverse impacts on tunnel stability. To ensure the serviceability of existing tunnels, this paper presents experimental and numerical studies with reference to a foundation pit case history excavated above twin-tube shield tunnels in soft soils. The experimental tests were firstly applied to study the deformation characteristics and structural response of the shield tunnels. Thereafter, an extensive numerical investigation was performed to determine the influence of some factors such as cover-to-excavation depth ratio, length-to-depth ratio, and unloading ratio on tunnel displacement behaviors. It was demonstrated that the tunnel heaves as the excavation proceeds, and heaves and horizontal displacements reach their maximum values when the excavation is finished. The earth pressure around the tunnels is symmetrically distributed in a gourd shape, with a larger reduction at the tunnel crown and invert and a smaller reduction at tunnel side walls. Additionally, the earth pressure at the tunnel crown and invert changes more significantly than that at other parts. The tunnel moment increment is significantly affected by the tunnel excavation depth. The axial force at or near the side walls of the tunnel is the most sensitive to the unloading effect induced by the excavation activity.